(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: The supervisory function is an essential part of the management process Operational Assistance (BOS). The purpose of this research is to find out how the supervisory functions of the Fund School operational assistance (BOS) by Education Office city of Manado. The research method used is descriptivequalitative method. The location of the research on select three SDN from SDN 04 Manado, Manado, and SDN 21, SDN 100 Manado. Informant research as many as eight people: Head of education city of Manado (one person), the management team School operational assistance BOS from city Education Office (one person), Headmaster (three people) and a school Committee/student parents People (three people) data collection Techniques used are interviews. Data analysis was done with a descriptive-qualitative analysis techniques, interactive model of the Miles and Hubernann. Based on research results drawn conclusion: The supervisory function and Operational Assistance School by the education service Manado well implemented through the use of the means/methods of supervision that exists: the implementation of the technical instructions consistently BOS by schools, socialization and coaching against the school in the management and reporting of the Fund’s School operational assistance (BOS), monitoring or monitoring on a regular basis, the implementation of the reporting system by the BOS of the school funds on a regular basis, and the evaluation of the implementation of the Fund’s School operational assistance (BOS) at the school. Referring to the conclusions of the study results presented suggestions: (1) to be more effective the supervisory functions of the Fund’s boss, let the Manado City Education Office parties set the school superintendent accompanying the management team School operational assistance (BOS) in doing the monitoring and supervision of fund management School operational assistance (BOS) at school. (2) the functional Supervision by supervisory internal functional apparatus (inspectorates or supervisory area) need to be implemented to support the supervisory funded by the management team of the city Education Office School operational assistance (BOS) in supervising and checking the use and the School operational assistance BOS at the school. This is important to prevent diversion/use of funds misappropriation by the School operational assistance (BOS) of the school. Keywords: Functions Of Surveillance, Fund School operational assistance (BOS)